Intraspecific morphological variation and environmental drivers in Macleania rupestris: a model-based population classification - Peña, Denisse F.; Villena, Paulina; Curillo, Diana; Jiménez, Carlos A.; Ordoñez, Eduardo; Jadán, Oswaldo (Frontiers in Plant Science, 2025)
IntroductionMacleania rupestris, an ecologically and culturally important species of the Ericaceae family, inhabits the montane forests of southern Ecuador and exhibits significant but understudied intraspecific morphological variation. Understanding this variation and its environmental drivers is crucial for effective conservation and restoration planning, particularly in a changing climate.MethodsWe analyzed 15 quantitative traits in 200 individuals from four populations located in the Azuay and Cañar provinces to identify morphological groups and assess their environmental drivers. Hierarchical clustering and Random Forest classification were employed to detect distinct morphological groups. Additionally, generalized linear models were used to evaluate the influence of climatic seasonality and spatial autocorrelation on the most relevant traits.ResultsWe identified two distinct morphological groups, primarily differentiated by seed number per fruit, fruit humidity, fruit length and width, and petiole length traits that together explained over 75% of the observed variation. Climatic seasonality and spatial autocorrelation significantly influenced these key traits. Notably, seed number and fruit length responded strongly to variations in temperature and precipitation, while traits such as fruit humidity and petiole length showed moderate sensitivity to environmental gradients. A Random Forest classification model, based on the most relevant traits, achieved 99.5% accuracy, enabling robust assignment of new individuals into morphological groups.DiscussionOur findings highlight the influence of environmental heterogeneity on intraspecific differentiation in M. rupestris and provide evidence for local adaptation along climatic gradients. This study offers a novel framework for trait-based classification and emphasizes the importance of integrating morphological variation and environmental factors into conservation planning. By identifying environmentally driven morphological groups, these results can inform seed sourcing strategies and restoration efforts aimed at enhancing ecosystem resilience in the montane forests of southern Ecuador.